Consumption and social integration: Empirical evidence for Chinese migrant workers - Xiaobing Huang; Xiaolian Liu (Kiel Institute for the World Economy (IfW), 2016)
This paper investigates the nexus between consumption and social integration of Chinese migrant workers using survey data with 869 samples from four Chinese provinces. The study suggests the following results: (1) Migrant workers are less integrated in terms of psychological integration and cultural integration, but they are strongly motivated to integrate into host societies; (2) An increase in consumption is associated with an increase in the social integration of migrant workers. This effect is stronger for new-generation migrant workers and weaker for high-income migrant workers; (3) Entertainment consumption plays the most important role in the social integration of migrant workers, whereas the effect of housing consumption on social integration is found to be negative; (4) Among all types of consumption behaviors, rational consumption is beneficial to the social integration of migrant workers, whereas impulsive consumption is harmful. The effects of economic consumption and conspicuous consumption are not significant.
Keywords: F22; J15; D73; K42; 330; consumption; consumption behavior; migrant workers; social integration